Students’ feedback- An effective tool towards enhancing the Teaching Learning Process - Mangla, Monika; Mehta, Vaishali; Pattnaik, Chinmay Ranjan; Mohanty, Sachi Nandan (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: Evaluation is a key activity to improve the quality of service in every domain. However, it becomes quite challenging to measure the performance in some areas. Teaching is one such domain where it is bit intricating to evaluate the performance of teaching community. Here, in this work, authors have proposed effective usage of students’ feedback to enhance the quality of teaching learning process. OBJECTIVES: The objective of this paper is to scientific and well-defined approach for teacher’s performance evaluation. This can help the faculty to identify the strengths and weaknesses of their teaching and evaluation methods. METHODS: Data analysis and data visualization techniques have been used gain useful insights of the stduents’ feedback on various parameters. In order to carry out the simulation, authors have considered the teaching learning process in an engineering college. RESULTS: It is evident from the results obtained 12 that more than 50% agree that the feedback system is fare and beneficial for the quality improvement in teachers. CONCLUSION: Such analysis not only provides the useful insights regarding avenue for im-provement, but also helps the management for appraisals to outperforming teachers.